PERAN MEDIA FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Puput Ambaryuni; Wiwik Hidayati; Nuni Widiarti; Decky Avrilianda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Research regarding 21st-century learning emphasizes the critical need for high-level thinking skills, yet many elementary schools still rely on conventional, non-interactive media. This study aims to analyze the role of flipbook media in enhancing the critical thinking skills of elementary school students. The research employs a Systematic Literature Review (SLR) method, involving stages such as keyword identification, literature searching, inclusion and exclusion criteria determination, analysis, synthesis, and final reporting. Data were gathered using the Publish or Perish application, which initially yielded 100 articles; these were subsequently filtered down to 11 selected articles for descriptive analysis. The findings indicate that flipbook media plays a significant role in improving elementary students' critical thinking, specifically in areas of analysis, evaluation, and problem-solving. This improvement is attributed to the interactive characteristics of flipbooks, which include features like animation, audio, and video that encourage active student engagement. Furthermore, the use of flipbooks was found to boost student learning motivation and conceptual understanding. Consequently, flipbook media serves as an innovative and effective alternative solution to support the development of critical thinking skills in elementary education.